Load distribution in edge-stiffening beam of a simply supported bridge deck - Kusuma, Iwan Permadi (2005)
This study involves two distinct methods for analysis of a simply supported bridge deck with or without edge-stiffening beam and the effect of edge-stiffening on the longitudinal and transverse moments along the deck. An analysis of a slab bridge with or without edge-stiffening beams is made and the result obtained from LUSAS programs (Finite Element Method) are compared with those derived theoretically (Load Distribution Method). The analysis considered HB loading acting on deck bridge. The analysis is confined to the case where the effective depth of the bridge is constant between the edge-stiffening. The degree of accuracy to be expected from the theoretical analysis and the difference in the longitudinal and transverse bending moment due to the effect of edge-stiffening beams are estimated. Part of the analysis for the above problems involves the determination of longitudinal moment in the corner or edge-stiffening beam.